2017
DOI: 10.1080/10826084.2017.1349796
|View full text |Cite
|
Sign up to set email alerts
|

Between Traditions and Health: Beliefs and Perceptions of Health Effects of Smokeless Tobacco Among Selected Users in Nigeria

Abstract: The study concludes that there is a need to focus on the control of SLT because this product is a major alternative to tobacco smoking among indigenous African populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The fact that the consumption of smokeless tobacco prevails among women is in accordance with the observed in other Eastern sub-Saharan countries, named Burundi, Malawi and Zambia [16]. Previous studies suggested that smokeless tobacco users perceived this form of consumption not only as harmless but also with some health benefits [17,18]. In addition, the fact that women are socially and economically more vulnerable than men may explain the more frequent use of cheaper forms of tobacco among them.…”
Section: Trends In the Past 10 Yearssupporting
confidence: 81%
“…The fact that the consumption of smokeless tobacco prevails among women is in accordance with the observed in other Eastern sub-Saharan countries, named Burundi, Malawi and Zambia [16]. Previous studies suggested that smokeless tobacco users perceived this form of consumption not only as harmless but also with some health benefits [17,18]. In addition, the fact that women are socially and economically more vulnerable than men may explain the more frequent use of cheaper forms of tobacco among them.…”
Section: Trends In the Past 10 Yearssupporting
confidence: 81%
“…A study from Bangladesh showed that SLT was considered to be a remedy for toothache though almost all participants accepted that these products caused heart disease, cancer and tuberculosis 5 . A recent study from Nigeria revealed that SLT users believed it to aid in sleep, protect against cold and act as a cure for headaches, apart from giving a ‘feel of high’ 6 .…”
mentioning
confidence: 99%
“…These findings suggest that the monitoring of pictorial health warnings on tobacco product packaging as prevention efforts/measures is warranted. products 16 . Tobacco warning labels are a useful tobacco control tool, however research has shown that attention to warnings and exposure to current health warning labels is lowest among individuals with lower education and income 17,18 .…”
Section: Introductionmentioning
confidence: 99%